2007
DOI: 10.1007/s11605-006-0031-9
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Perforations in Behçet’s Disease

Abstract: Behçet's disease accompanied by intestinal involvement is called intestinal Behçet's disease. The intestinal ulcers of Behçet's disease are usually multiple and scattered and tend to perforate easily, so that many patients require emergency operation. The aim of this study is to determine the extent of surgical resection necessary to prevent reperforation and to point out the findings of concurrent oral and genital ulcers and multiple intestinal perforations in all patients of our series. During a 25-year stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 31 publications
1
18
0
3
Order By: Relevance
“…Mucosal inflammation and ulceration may occur throughout the GIS with typical ulcers are usually located in the ileocecal area by 88% [1,3,14,[38][39][40]. Ulcers are mostly wider than 1 cm, round-oval shaped (77%), single (67%) or several located seperately (27%), sharply circumscribed, staple hole-like or perforated [1][2][3]11,38,41] (Figures 1A,1B and 2). Figure 1.…”
Section: Macroscopic Findingsmentioning
confidence: 99%
“…Mucosal inflammation and ulceration may occur throughout the GIS with typical ulcers are usually located in the ileocecal area by 88% [1,3,14,[38][39][40]. Ulcers are mostly wider than 1 cm, round-oval shaped (77%), single (67%) or several located seperately (27%), sharply circumscribed, staple hole-like or perforated [1][2][3]11,38,41] (Figures 1A,1B and 2). Figure 1.…”
Section: Macroscopic Findingsmentioning
confidence: 99%
“…Chou ve ark.nın kendi kliniklerinde Behçet hastalığına bağlı intestinal perforasyon nedeni ile opere ettikleri 21 hastayı inceledikleri geriye dönük çalışmalarında ve Kasahara ve ark.nın Behçet hastalığı-na bağlı 136 perforasyon olgusunun verilerinin geriye dönük incelenmesinde de BH'nin sistemik bulgularının ve tanısının ortalama üçüncü dekatta koyulduğu ve GİS tutulumu ve perforasyonlar ile en sık dördüncü dekatta karşılaşıldığı saptanmıştır. [9,10] Bizim burada sunduğumuz olgunun hem 19 yaşında olması, hem de tanı ile eşzamanlı olarak intestinal tutulum ve perforasyon olması ilgi çekicidir.…”
Section: Olgu Sunumuunclassified
“…[9,10] Biz olgumuzda sağlam cerrahi sınırlar bırakılacak şekilde parsiyel ince bağırsak rezeksiyonu uyguladık ve karın içerisi kirli olduğundan dolayı primer anastomoz yerine tüfek namlusu ileostomi oluşturarak operasyonu sonlandırdık. Rezeksiyon sonrası primer anastomoz yerine ileostomi tercih edilmesi ve elektif ileostomi kapatılması, hastalığın aktive olduğu bu dönemde uygulanan primer anastomoz sonrası görü-len perianastomotik reperforasyon komplikasyonu oranlarını da azaltabileceğini düşündürse de, bu cerrahi tekniğin başarı oranlarını ortaya koymak için geniş olgu çalışmalarına ihtiyaç vardır.…”
Section: Olgu Sunumuunclassified
“…Deep ulcers in the GI tract that are seen in BD are the major causes of severe complications, such as severe bleeding and perforation. There are only a few studies that have reported colonic perforations due to BD (2,3). In this article, we report a patient with BD who underwent an emergent operation because of acute abdomen, developing secondary to multiple perforations of the ascending colon and terminal ileum.…”
mentioning
confidence: 96%
“…They can be observed anywhere from the lip to anus and lead to severe complications, requiring surgical treatment (2,4,5). Treatment and follow-up of the patient requires a team approach, including a general surgeon, rheumatologist, and gastroenterologist.…”
mentioning
confidence: 99%